Electrotechnological system for monitoring effects of optical range electromagnetic fields on vegetation bioobject - Nikiforova, L.; Kizim, I.; Bogatyrev, Yu. (Технічна електродинаміка, 2014)
The question of application of sources of light on light-emitting diodes in hothouses is considered. The necessity of development of complex for registration of bioelectric potentials of plants, necessity for working off technology of growing of plants with the use of lamps on light-emitting diodes is grounded. The developed measuring complex allows to influence on vegetable bioobjects with LED (laser) SOR and to estimate the response in real time. Size of BEP reflects real processes of a metabolism and is inseparably linked with a physiological condition of a live organism, and the steady nonequilibrium state in vegetable organisms is supported due to processes of a metabolism continuously proceeding in them. Thus, at research of various ways of stimulation of development of VBO measurement of size BEP can be used for an assessment of a functional condition of VBO at different stages of an organogenesis. Рассмотрен вопрос использования полупроводниковых светодиодных и лазерных источников оптического излучения (ИОИ) в условиях закрытого грунта. Обоснована структура электротехнологического комплекса контроля влияния электромагнитных полей оптического диапазона на растительные биообъекты путем регистрации биопотенциалов растений. Разработанный измерительный комплекc позволяет влиять на растительные биообъекты (РБО) светодиодными (лазерными) ИОИ и оценивать ответную реакцию в режиме реального времени. Величина биоэлектрического потенциала (БЭП) отражает реальные процессы обмена веществ и неразрывно связана с физиологическим состоянием живого организма, а устойчивое неравновесное состояние в растительных организмах поддерживается за счет непрерывно протекающих в них процессов обмена веществ. Таким образом, при исследовании различных способов стимулирования развития РБО измерение величины БЭП может использоваться для оценки функционального состояния РБО на разных стадиях органогенеза. Розглянуто питання використання напівпровідникових світлодіодних і лазерних джерел оптичного випромінювання (ДОВ) в умовах захищеного ґрунту. Обґрунтована структура електротехнологічного комплексу контролю впливу електромагнітних полів оптичного діапазону на рослинні біооб'єкти (РБО) шляхом реєстрації біопотенциалів рослин. Розроблений вимірювальний комплекс дозволяє впливати на рослинні біооб'єкти світлодіодними (лазерними) ДОВ і оцінювати реакцію у відповідь в режимі реального часу. Величина біоелектричного потенціалу (БЕП) відображає реальні процеси обміну речовин і нерозривно пов’язана з фізіологічним станом живого організму, а стійкий нерівноважний стан в рослинних організмах підтримується за рахунок безперервно протікаючих в них процесів обміну речовин. Таким чином, при дослідженні різних способів стимулювання розвитку РБО вимірювання величини БЕП може використовуватися для оцінки функціонального стану РБО на різних стадіях органогенезу.